A Vasculitis-Associated Neuromuscular and Vascular Hamartoma Presenting as a Fatal Form of Abdominal Cocoon. (February 2019) - Pattnaik, Sandeep Abhijit; Mitra, Suvradeep; Mishra, Tushar Subhadarshan; Purkait, Suvendu; Kumar, Pankaj; Naik, Suprava
Neuromuscular and vascular hamartoma (NMVH), also known as neuromesenchymal hamartoma, is a rare hamartomatous condition of the intestine. It usually presents with submucosal humps protruding in the intestinal lumen causing obstructive features. The other clinical manifestations are hematochezia or melena and protein-losing enteropathy. The etiopathogenesis of these lesions is not well known, although an association with small bowel Cröhn's disease and diaphragm disease had been postulated, the latter related to chronic nonsteroidal anti-inflammatory drug intake. Only 24 cases of NMVH are reported in the English literature and all of them could be adequately cured by resection of the affected part of the bowel. Moreover, none of these cases presented with abdominal cocoon or showed any evidence of vasculitis. We describe a peculiar case of NMVH in a 45-year-old male who presented with abdominal cocoon with symptomatic recurrence and fatal outcome within a month of surgery. Histopathology revealed classical histomorphology of NMVH with evidence of vasculitis. This appears to be the first case of a fatal form of NMVH, presenting with abdominal cocoon and associated with vasculitis.